Statistical Modelling of Occupant Behaviour - Møller, Jan Kloppenborg (CRC Press LLC, 2024)
This book is the result of a collaboration between researchers from occupant behaviour and statistical modelling. It presents a range of statistical methods and models used for modelling occupancy behaviour